1997
DOI: 10.1097/00004728-199705000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note. 3D Virtual Endoscopy of the Upper Airway: Optimization of the Scan Parameters in a Cadaver Phantom and Clinical Assessment

Abstract: Our goal was to evaluate the influence of the scan parameters on the 3D virtual endoscopy of the larynx and trachea and the clinical assessment. Helical CT (HiSpeed Advantage; GE, Milwaukee, WI, U.S.A.) of a cadaver phantom was performed with increased collimation (1-10 mm) and pitch (0.5-3). Seventy-two patients with complaints of the upper airways were investigated by virtual endoscopy and their results were compared with the findings of regular endoscopy. Best correlation between virtual endoscopy and anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 11 publications
2
35
0
Order By: Relevance
“…All space occupying tumours w5 mm in diameter were demonstrated using SSD VB [32]. However, mild stenoses, submucosal infiltration, and superficial spreading tumours are not identified [32,33].…”
Section: Central Airwaysmentioning
confidence: 95%
See 2 more Smart Citations
“…All space occupying tumours w5 mm in diameter were demonstrated using SSD VB [32]. However, mild stenoses, submucosal infiltration, and superficial spreading tumours are not identified [32,33].…”
Section: Central Airwaysmentioning
confidence: 95%
“…virtual bronchoscopy (VB)) produce remarkably high-quality and accurate reproductions of major endoluminal abnormalities ( fig. 2) [19,32,33]. VB has some advantages over real bronchoscopy: it is noninvasive, recurrent views can be created, and directions of view of the virtual endoscope may be changed interactively.…”
Section: Central Airwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] In one study endoluminal space-occupying lesions of greater than 5 mm and stenosis of greater than 50% were detected quickly by virtual endoscopy in all cases. In addition, altered configurations based on external compression were always correctly identified.…”
mentioning
confidence: 91%
“…It has been concluded that the upper limit for collimation is either 5 mm with a pitch of 1 or 3 mm with an increased pitch of 2 mm. [37] For practicality, it was determined that a collimation of 3 mm with a pitch of 1.5 mm and an overlapping reconstruction with an increment of 1 mm is optimum. These parameters maximize the data for producing 3-D reconstruction while minimizing the amount of radiation used in obtaining the study.…”
mentioning
confidence: 99%